Improvement of problem solving skills and cognitive learning outcomes through implementation of guided inquiry learning model on biology subject - Widyaningsih, Syahida; Ibrohim, Ibrohim; Sumberartha, I. Wayan (AIP conference proceedings, 2021)
The research that has been carried out aims to find out the improvement of problem solving skills, with student cognitive learning outcomes and to find out the relationship of problem solving skills with students’ cognitive learning outcomes using guided inquiry models. This research was conducted by the Classroom Action Research method which supported the correlation. The research approach used for Classroom Action Research is a qualitative and quantitative approach, in the first cycle basic competension 3.7 digestive system material and second cycle basic competension 3.8 respiratory system material supported by lessen study activities. While the research approach used for correlation research is quantitative by using the value of the second cycle. For quantitative data Classroom Action Research was analyzed using the N-gain formula. Whereas the correlation research approach was tested using SPSS Windows 16 analysis. The technique of collecting data is done by using the results of a written test containing essay questions and learning achievement data obtained from observations. The subject of this research is class students XI MIPA 4 Malang Senior High School, to 34 students. The results of the class action study found that there was an increase in the problem solving skills of the N-gain Cycle I results and the second cycle was 11.76%, the cognitive learning outcomes of the students there was an increase in the N-gain cyclical I and cycle II were 5.40%. While the results of the correlation study there is a relationship between problem solving skills with students’ cognitive outcomes with a coefficient value of 0.529 moderate correlation.